Theology of Humanity in the Sufism Community of the Sabbaqal Mufarridiyah Group in Pekalongan Indonesia - Maulana, Luthfi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
Theology of humanity is a development of previous theology which discusses about divinity and its characteristics then develops not only to discuss about God, but more about human relations with each other as a manifestation of the closeness of human relations to their Lord. At this stage then theology was connected with social matters of humanity and gave birth to the theology of humanity. This paper discusses the principles of human theology based on God and how the motives and the process of implementing the theology of humanity are run by the community of the Sabbaqal Mufaridiyyah community. The method usedis the analysis of Emile Durkem Social Solidarity and Max Weber's social action analysis to find out the motives and objectives of the establishment of this theological theology of humanity. The results of this study are the Sabbaqal Mufarridiyah who has produced a sufism community that does not focus on transcendent theology but humanity theology through the role of Mufarridiyah community in various social activities such as helping the community in the form of medical help, alleviating problems, and resolving economic problems experienced by the community especially between sufism community of Mufarridiyah.